Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd007924.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Medical interventions for high grade vulval intraepithelial neoplasia

Abstract: Background Vulval intraepithelial neoplasia (VIN) is a pre-malignant condition of the vulval skin; its incidence is increasing in women under 50 years. VIN is graded histologically as low grade or high grade. High grade VIN is associated with infection with human papilloma virus (HPV) infection and may progress to invasive disease. There is no consensus on the optimal management of high grade VIN. The high morbidity and high relapse rate associated with surgical interventions call for a formal appraisal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…However, a smaller retrospective review of 93 patients by Hillemans et al (11) showed no significant difference in recurrence between wide local excision (41.7%) and laser ablation (40.4%), but no recurrences were found among 7 patients treated with vulvectomy. Finally, imiquimod has been shown to be effective vs. placebo, but there is a lack of research comparing this treatment to other common interventions for VIN 2/3 (12). Our data suggest imiquimod may be superior to laser ablation in preventing recurrence, but prospective evaluation is needed.…”
Section: Discussionmentioning
confidence: 80%
“…However, a smaller retrospective review of 93 patients by Hillemans et al (11) showed no significant difference in recurrence between wide local excision (41.7%) and laser ablation (40.4%), but no recurrences were found among 7 patients treated with vulvectomy. Finally, imiquimod has been shown to be effective vs. placebo, but there is a lack of research comparing this treatment to other common interventions for VIN 2/3 (12). Our data suggest imiquimod may be superior to laser ablation in preventing recurrence, but prospective evaluation is needed.…”
Section: Discussionmentioning
confidence: 80%
“…VIN and vulval cancer are being increasingly diagnosed in younger women for whom surgical options are unlikely to be readily accepted. The previous version of this review called for more high-quality trials on medical treatment options for VIN (Pepas 2011). We continue to update this review on the medical alternatives to surgery, to inform women's choices, to support clinical guidelines, and to stimulate VIN research.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 98%
“…37,38 Most studies and research relate to full thickness VIN. Multifocal lesions can be treated in the same manner as single lesions, but may have a higher recurrence rate.…”
Section: Management Further Investigationmentioning
confidence: 99%